Exploration of proton transfer pathways in the oxygen-tolerant [NiFe]-hydrogenase from Escherichia coli - Brooke, E (2017)
Hydrogenases catalyse the interconversion of molecular hydrogen with protons and electrons. Thus, they are of significance due to the growing interest in a hydrogen economy, which would serve to replace fossil fuels. Hyd-1 is a [NiFe]-hydrogenase from Escherichia coli and, unlike many hydrogenases, it is capable of hydrogenases oxidation in the presence of oxygen. Understanding the mechanism of hydrogen activation by Hyd-1 is, therefore, paramount to the rational design of synthetic analogues which may be used in hydrogen technologies. In this thesis, the role of several conserved carboxylate residues in [NiFe]-hydrogenases – E28, D118 and D574– has been explored using Protein Film Electrochemistry (PFE), solution assays and X-Ray crystallographic structures. PFE is a technique used in the study of redox proteins, including [NiFe]-hydrogenases. Precise potential control means that a detailed picture of an enzyme’s thermodynamic and kinetic characteristics can be elucidated. D118 and D574 form a canopy above the NiFe active site with the conserved arginine R509, which has recently been implicated as the base in hydrogen oxidation. Although the high levels of conservation for these enzymes suggest an active role in hydrogen oxidation, the rates of variants D574N and D118N/D574N indicate that they are not crucial to Hyd-1. Instead, D118 appears to have a role in controlling gas access to the active site and D574 is important for ensuring a wide potential window for hydrogen oxidation in the presence of oxygen. Previous studies with E28 variants in a standard [NiFe]-hydrogenases have indicated that this highly conserved residue is part of an extended proton transfer network. The variant E28Q has unusual activity at high potential, which suggests that the role of E28 is more complex. This work has raised some interesting questions that require further exploration.